Strongly Luminescent Dion–Jacobson Tin Bromide Perovskite Microcrystals Induced by Molecular Proton Donors Chloroform and Dichloromethane. (29th April 2021) - Wang, Shixun; Popović, Jasminka; Burazer, Sanja; Portniagin, Arsenii; Liu, Fangzhou; Low, Kam‐Hung; Duan, Zonghui; Li, Yanxiu; Xiong, Yuan; Zhu, Yuanming; Kershaw, Stephen V.; Djurišić, Aleksandra B.; et al.
Abstract: Lead‐free 2D perovskites based on tin halide octahedron slabs with Dion–Jacobson (DJ) phases have drawn attention due to their improved stability; still, reports on light‐emitting DJ lead‐free perovskites are scarce. Herein, a room‐temperature ligand assisted re‐precipitation method is used to produce ODASnBr4 perovskite microcrystals (ODA denotes protonated 1, 8‐octanediamine). After incorporating molecular dopants chloroform and dichloromethane, not only the crystallinity of the DJ perovskite phase improves, but their emission becomes much stronger due to the formation of hydrogen bonds between [SnBr6 ] 4− octahedra and acidic CH proton donors. ODASnBr4 microcrystals doped with these molecules show a high photoluminescence quantum yield (PLQY) approaching 90%, and their emission remains stable under a continuous UV irradiation, with less than 10% loss in intensity over 6 h. Moreover, by tuning the pristine ODASnBr4 with various degrees of exposure to the molecular dopants, the maximum of their self‐trapped exciton emission can be fine‐tuned over a spectral range of 570–608 nm while maintaining high PLQYs of 83–88%. This provides a convenient way to adjust the spectral position of DJ perovskite emission without changing halides or A‐site spacers. Thus, stable and strongly emitting lead‐free DJ perovskite materials have been developed. Abstract : Small molecule dopants containing acidic CH proton donors, such as chloroform and dichloromethane stretch octahedron slabs in Dion–Jacobson tin bromide perovskites by forming hydrogen bonds, which result in their enhanced stability, photoluminescence quantum yields approaching 90%, and tunable emission maxima.